(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Malaria remains a major public health challenge in tropical and subtropical regions, and understanding the knowledge and practices of individuals regarding its prevention and control is crucial for effective disease management. This study investigates the knowledge and practices of malaria prevention and control measures among respondents in relation to sociodemographic characteristics. Objective: To assess the level of knowledge and practices of malaria prevention and control measures and to explore associations with sociodemographic factors such as age, educational background, marital status, occupation, income, and parity. Method of Analysis: A cross-sectional study design was used, involving 200 respondents. Data were collected using a structured questionnaire and analyzed using descriptive and inferential statistics. Chi-square tests were employed to examine associations between respondents’ knowledge and sociodemographic characteristics. Results: The study revealed high levels of knowledge regarding malaria prevention, with 90% of respondents aware of the importance of draining stagnant water, 95% using prescribed antimalarial medications, and 80% clearing bushes around residential areas. However, practices of malaria prevention were less consistent, with only 50% always engaging in regular house fumigation, 75% consistently using mosquito-repellent creams, and 70% sleeping under long-lasting insecticidal nets (LLINs). Significant associations were found between sociodemographic factors and knowledge levels. A higher proportion of respondents with tertiary education (90%), stable employment (83.3%), and higher income (80%) demonstrated good knowledge of malaria prevention. Age (p=0.045), educational background (p=0.027), marital status (p=0.052), occupation (p=0.008), and income (p=0.001) were significantly associated with knowledge of preventive measures. Respondents in the age group 25-34 years showed the highest knowledge (87%), while those in the 15–25 years’ group had the lowest (50%). Employed individuals showed better practices (83.3%) compared to their unemployed counterparts (62.5%). Conclusion: The findings highlight the significant role of sociodemographic factors in shaping both knowledge and practices of malaria prevention. While respondents demonstrated a good understanding of preventive measures, challenges in translating knowledge into practice remain. Targeted interventions addressing educational gaps and socioeconomic disparities are essential to improving malaria prevention and control efforts in endemic regions.